Decision to Emigrate Amongst the Youth in Lebanon - Ghassan Dibeh; Ali Fakih; Walid Marrouch (Institute of Labor Economics (IZA), 2017)
This paper studies the determinants of youth emigration decisions, which is considered to be one of the main causes of 'Brain Drain' in Arab Mediterranean Countries (AMCs). We focus on the case of Lebanon using a unique dataset covering young people aged 15 to 29 from the year 2016. The aim of the paper is to identify the profile of youth's propensity to emigrate from Lebanon. The empirical results indicate that youth from non-wealthy backgrounds living in smaller dwellings have a higher propensity to emigrate. It is also found that being male and unemployed has a positive incidence on migration. Moreover, university education promotes the willingness to emigrate; while residents of poor regions are more likely to express such willingness. Finally, the paper provides some insights for policymakers.
Keywords: C25; J60; O15; 330; emigration; youth; Lebanon; probit model